Effects of stereoscopic artificial floating wetlands on nekton abundance and biomass in the Yangtze Estuary. (September 2017) - Huang, Xiaofeng; Zhao, Feng; Song, Chao; Gao, Yu; Geng, Zhi; Zhuang, Ping
Abstract: Habitat degradation is one of the greatest existing threats to nekton biodiversity in estuarine and coastal habitats. Stereoscopic artificial floating wetlands (SAFWs) can provide new nekton habitats and have been widely used as conservation and management tools in freshwater and marine environments. In the current study, we constructed Phragmites australis SAFWs: the P. australis rhizomes were planted on the artificial floating beds, and palm slices were hung under the floating platforms to act as submerged plants. These SAFWs were anchored in the north channel of the Yangtze Estuary. To determine if SAFWs can serve as fish aggregation devices, fishes and crustaceans were sampled monthly using a bottom lift net during high-tide from July to October 2014. Our assessment was based on environmental parameters, nekton density, nekton species composition and the total length of the three most abundant fishes at the experimental and control sites. Nekton abundance was approximately three times greater in the SAFWs than that in the control habitats (108.2 ± 27.56 ind./m 2 vs. 28.37 ± 15.88 ind./m 2, respectively). There were no significant habitat-specific differences in the size distribution of the three most abundant fish species ( Acanthogobius ommaturus, Odontamblyopus rubicundus and Eleutheronema tetradactylum ) because most of the individuals sampled were juveniles. This study demonstrates that SAFWs can form stable environments for nekton and increase habitat available to juvenile fish. Highlights: The Phragmites australis stereoscopic artificial floating wetlands create new habitats for nekton in the Yangtze Estuary. Both the P. australis and palm sheets on the SAFWs alter the surrounding water characteristic. The P. australis SAFWs can be used as fisheries conservation and management tools in coastal and estuarine areas.